Association between low cortical bone mineral density, soft-tissue calcification, vascular calcification and chondrocalcinosis: a case-control study. Issue 11 (2nd August 2013) - Abhishek, A; Doherty, S; Maciewicz, R; Muir, K; Zhang, W; Doherty, M
Abstract : Objectives: To examine the association between bone mineral density (BMD), soft-tissue calcification, vascular calcification and chondrocalcinosis (CC). Methods: A case-control study within the Genetics of Osteoarthritis and Lifestyle (GOAL) database (n=3170). All GOAL participants completed a questionnaire self-reporting current and early adult life exposures. Radiographs of knees, hands and pelvis were scored for osteoarthritis (OA), CC, pelvic vascular calcification, peri-articular knee calcification and metacarpal index (MCI—measure of cortical BMD). Calcaneal dual-energy X-ray absorptiometry (DEXA) was performed. Cases had radiographic CC, while controls did not have CC at any radiographed site. OR, 95% CI were used to measure association between risk factors and CC. Logistic regression was used to adjust for confounding and to estimate the adjusted OR (aOR). Results: Low MCI (aOR (95%) for CC in 1st tertile 1.41 (1.06 to 1.89), with 3rd tertile referent), soft-tissue calcification (aOR (95%) for CC 1.81 (1.36 to 2.42)), and vascular calcification (aOR (95%) for CC 1.76 (1.13 to 2.75)) independently associated with CC. There was a negative association between body mass index and CC (aOR (95%) for CC in 2nd and 3rd tertiles 0.68 (0.53 to 0.89), and 0.67 (0.51 to 0.88) respectively with 1st tertile referent). Age and OA associated with CC. However, only age and low MCI independently associated with CC at >1 joint. Self-reported meniscectomy, low cortical BMD, vascular calcification, and soft-tissue calcification independently associated with knee CC. Conclusions: This study identifies several novel associations of CC including low cortical BMD. The association between vascular calcification, soft-tissue calcification, and CC suggests a generalised constitutional predisposition to calcium crystal formation.